OPERATING EXPERIENCE GAROTA STRUCTURES IN UKRAINE AND THE WORLD - Маджд, С. М. (Science-based technologies, 2016)
The brought results over of analysis of the use of bioengineering building for providing of environmental safety hydroecosystems in Ukraine and different countries of the world. The well-proven advantages of the use of methods of fitotechnologies are in relation to the traditional methods of proceeding in quality of water ecosystems. Lighted up modern state and experience of exploitation of bioengineering building in the different countries of the world for cleaning of effluents in different industries of production. Considered basic types of engineer-biological building on the basis of the closed bioplateau of hydroponnogo type, that used in Ukraine. Experience of the use of the hydrobiotechnological systems is analysed in Ukraine of intended for the deep cleaning and overflow-pipe of service-utility, productive and rain waters in the stream of subsoil waters or in superficial reservoirs. It is shown that lately in our country, bioplateaux began widely to apply as local sewage treatment plants of small power for cottages and building in that absent tricking into to the sewage system, for the filling stations, washings of automobile and freight transport, objects of car-care center.